Академічна доброчесність як невід'ємна складова сучасної вищої освіти - Шлєіна, Людмила Іванівна; Shlieina, Liudmyla (Запоріжжя : 2023, 2023)
UA: У статті розглянуто поняття «академічна доброчесність» у площині законодавчої бази. Узагальнення досліджуваного поняття та його змістових частин у межах державного законодавства та кодексу честі університету дало змогу визначити форми, причини та методи запобігання й боротьби з академічною недоброчесністю. Доведено важливість створення умов для недопущення академічної нечесності в середовищі університетів та науково-професійній комунікації. EN: The paper considers the concept of «academic honesty» within legislative framework. The generalization of the concept under investigation and its constituent parts (plagiarism, intellectual property) in the framework of government legislation and honour codes of universities provided the possibility to define the forms and causes of academic dishonesty and determine the measures to prevent or fight against such a phenomenon. The importance to create necessary conditions to prevent academic dishonesty in university environment and scientific and professional communication has been proved.
Academic integrity as impossible component of modern higher education
Keywords: академічна доброчесність; академічна недоброчесність; наукова комунікація; academic honesty; academic dishonesty; scientific communication